Kinerja Simpang Tak Bersinyal Sultan Alauddin dan Monumen Emmy Saelan di Era New Normal - Winarno Saelan; Rais Rachman; Sufiati Bestari (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
The peak of traffic flow, the calculation of the intersection capacity, and the degree of saturation of the unsigned intersection referring to the Indonesian Highway Capacity Manual, 1997. This study aims to determine the degree of saturation of the unsigned intersection of Sultan Alauddin and Monumen Emmy Saelan Street, Makassar during the new normal period. The traffic survey on Monday and Thursday Indicated weekdays, the survey on Saturday indicated holidays. The vehicles enumerated were light vehicles, heavy vehicles, motorcycles, and unmotorized. The proportion of unmotorized and motorcycles was calculated in the analysis of intersection capacity. The Peak of traffic flow occurred in the afternoon which indicated the working days, the results are as follows, Q = 6917.3 pcu/hour, intersection capacity (C) = 4350,18 pcu/hour, degree of saturation (DS) = 1.59.